Optimum Design of Stiffened Plate-Structure Subjected to Static Loading - Al-Taee, Hatem H.; Al-Moosawy, Adil A.; Al-Shojary, Mohammed A. (Al-Khwarizmi Engineering Journal, 2018)
The field of structural optimization (optimal design) has grown rapidly over the past decades with many different optimization methods that could be used to produce a structure of minimum weight. This research deals with two aspects, in the first, a general numerical technique based on the finite element analysis and it suggests to investigate the preliminary behavior of metal stiffened plate under action of static load environment. The technique was included a finite element model of the structures using high- order isoparimetric plate elements to be used to create a certain models to obtain their optimum design. The models are characterized such that, each model is builded using different types of stiffener configuration. The second aspect was concerned with the investigation of the optimum design configuration of the structures. The optimization techniques used is called Morphing Evolutionary Structural Optimization (MESO). The Morphing ESO was examined in this research to be applied on stiffened plate structures. The Morphing ESO is based on the simple concept that by slowly removing efficient material from a structure, the residual shape evolves in the direction of making the structure better. The mathematical representation of this method is accomplished in this thesis with full programming and modification required being applicable to a new structure with a new condition. Where the thickness of the plate and stiffeners, and the stiffener height are the design variable. While the objective of the optimization is the structure weight and inequality constraints are the maximum Von Misses stress required for each structure.